New records of mayflies (Insecta: Ephemeroptera) from Bahia State, Northeastern Brazil - Lima, Lucas Ramos Costa; Knapp, Willian; Docio, Loyana (ENTOMOTROPICA, 2016)
This work presents a updated checklist of mayflies (Insecta: Ephemeroptera) from Bahia State, including new records of species based on collections performed between 2013 and 2014 in the Rio Grande Basin, West Region of Bahia, Northeastern Brazil. We add a brief biological note on ovoviviparity of Callibaetis radiatus Navás, 1920. A total of 350 specimens belonging to 13 species and 14 genera were collected and recorded for the first time, increasing from 41 to 54 the number of species in this state.